2016
DOI: 10.1016/j.str.2016.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Purine and Pyrimidine Nucleotides Bind to the HCN2 Ion Channel and Variably Promote C-Terminal Domain Interactions and Opening

Abstract: Cyclic AMP is thought to facilitate the opening of the HCN2 channel by binding to a C-terminal domain and promoting or inhibiting interactions between subunits. Here, we correlated the ability of cyclic nucleotides to promote interactions of isolated HCN2 C-terminal domains in solution with their ability to facilitate channel opening. Cyclic IMP, a cyclic purine nucleotide, and cCMP, a cyclic pyrimidine nucleotide, bind to a C-terminal domain containing the cyclic nucleotide-binding domain but, in contrast to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 42 publications
(66 reference statements)
5
27
0
Order By: Relevance
“…Current functional evidence in the HCN2 channel suggests that cAMP binding relieves tonic inhibition of the pore by an intracellular C-terminal region of HCN2 made up of the CNBD and a domain called the C-linker connecting the CNBD to the pore (Wainger et al, 2001). The structure of this CNBD and C-linker region of the HCN2 isoform was solved by x-ray crystallography in cyclic nucleotide-bound and unbound states, and it is a symmetrical tetramer (Zagotta et al, 2003;Taraska et al, 2009;Ng et al, 2016). A recent cryo-EM structure of the HCN1 isoform confirms that the channel is a symmetrical tetramer and also shows that the C-linker/CNBD regions, hanging below the pore, adopt a structure that is similar to the solved structure of the HCN2 C-terminus (Lee and MacKinnon, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current functional evidence in the HCN2 channel suggests that cAMP binding relieves tonic inhibition of the pore by an intracellular C-terminal region of HCN2 made up of the CNBD and a domain called the C-linker connecting the CNBD to the pore (Wainger et al, 2001). The structure of this CNBD and C-linker region of the HCN2 isoform was solved by x-ray crystallography in cyclic nucleotide-bound and unbound states, and it is a symmetrical tetramer (Zagotta et al, 2003;Taraska et al, 2009;Ng et al, 2016). A recent cryo-EM structure of the HCN1 isoform confirms that the channel is a symmetrical tetramer and also shows that the C-linker/CNBD regions, hanging below the pore, adopt a structure that is similar to the solved structure of the HCN2 C-terminus (Lee and MacKinnon, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge for understanding ligand sensitivity of pore opening in ligand-gated ion channels, including HCN channels, is to obtain a relevant measure of binding affinity directly by experiment (Colquhoun, 1998;Hines et al, 2014). We have developed an approach using isothermal titration calorimetry (ITC) to determine the affinity of cAMP for a freely occurring tetrameric form of the HCN2 C-terminus fragment containing the CNBD and C-linker (Chow et al, 2012;Ng et al, 2016). This C-terminus region is comprised of six α-helices in the C-linker and the four α-helices and eight β-strands that constitute the CNBD, and is identical to that solved by x-ray crystallography (Zagotta et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The hyperpolarization‐activated cyclic‐nucleotide‐gated (HCN) ion channels contribute to nerve impulse transmission and cardiac pacemaker activity in neurons and cardiomyocytes respectively . The HCN ion channels are tetramers that open during the repolarization phase of the action potential, resulting in a nonselective influx of positively charged ions and leading the membrane's resting potential toward the threshold for activation.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Ng et al (2016) systematically analyzed the interactions of canonical and non-canonical cNMPs with the hyperpolarization-activated cNMP-gated channel 2 (HCN2). In contrast to the prototypical HCN2 channel activator cAMP, cIMP failed to induce oligomerization of the cNMP-binding domains of the channel and opened ion conductance only ineffectively.…”
mentioning
confidence: 99%
“…Crystallographic studies revealed that cIMP and cAMP stabilize distinct HCN2 channel conformations. The study of Ng et al (2016) suggests that various cNMPs interact differentially with HCN channels, opening the door for specific pharmacological modulation of HCN channel subtypes in terms of full and partial activators and inhibitors.…”
mentioning
confidence: 99%